Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Solve by substitution?
y=4x-9
y=x-3 


Sagot :

We have such system
[tex] \left \{ {{y=4x-9} \atop {y=x-3}} \right. [/tex]
We can take first equation and put value of y in terms of x into second eq, so
y=x-3
4x-9=x-3             now we can solve it
4x-9=x-3       /-x both sides
3x-9=-3       /+9 both sides
3x=6           /:3 divide by 2 both sides
x=2 --- its the result